Assessing need for long-term oxygen therapy: a comparison of conventional evaluation and measures of ambulatory oximetry monitoring. - Russell KM; Ayo DS; Branca P; Rogers JT; Rodriguez M; Light RW (Respiratory Care, 2003)
BACKGROUND: Appropriate identification of hypoxic patients with chronic obstructive pulmonary disease (COPD) is important because of the demonstrated survival benefit of long-term oxygen therapy (LTOT) and its associated cost. Resting oxygen saturation (measured via pulse oximetry [S(pO2)]) and lowest exercise S(pO2) (during a 6-min walk test) is the standard method of determining LTOT requirements, but that method does not measure the patient's oxygenation during sleep or activities of daily living. We hypothesized that values obtained via the standard method would correlate poorly with values obtained via ambulatory oximetry monitoring. METHODS: We conducted a prospective, cohort study in an out-patient pulmonary clinic in a tertiary care referral center, with 20 stable COPD patients who were being evaluated for LTOT with conventional evaluation versus 16-24 hours of ambulatory oximetry. RESULTS: The resting S(pO2) did not correlate well with mean ambulatory S(pO2) (r = 0.64) or the percent of monitored time spent with S(pO2) < 88% (r = 0.49). The lowest exercise S(pO2) also did not predict mean ambulatory S(pO2) (r = 0.39) or the percent of monitored time spent with S(pO2) < 88% (r = 0.32). Conventional evaluation overestimated LTOT requirements with 16 of the 20 patients developing an S(pO2) < 88%, most of them with exercise only (ie, most had normal resting S(pO2)). With ambulatory monitoring, however, only 3 of the 16 patients spent > 10% of the monitored time with S(pO2) < 88%. CONCLUSION: There was a poor relationship between the conventional oxygenation assessment method and continuous ambulatory oximetry during LTOT screening with COPD patients.